Issues in stem cell plasticity - Filip, S; English, D; Mokrý, J (Journal of cellular and molecular medicine, 2004)
Experimental biology and medicine work with stem cells more than twenty years. The method discovered for in vitro culture of human embryonal stem cells acquired at abortions or from "surplus" embryos left from in vitro fertilization, evoked immediately ideas on the possibility to aim development and differentiation of these cells at regeneration of damaged tissues. Recently, several surprising observations proved that even tissue-specific (multipotent) stem cells are capable, under suitable conditions, of producing a whole spectrum of cell types, regardless, whether these tissues are derived from the same germ layer or not. This ability is frequently called stem cell plasticity but other authors also use different names - "non-orthodox differentiation" or "transdifferentiation". In this paper we wish to raise several important questions and problems related to this theme. Let us remind some of them: Is it possible to force cells of one-type tissue to look and act as cells of another tissue? Are these changes natural? Could these transformations be used to treat diseases? What about the bioethic issue? However, the most serious task "still remains to be solved - how to detect, harvest and culture stem cells for therapy of certain diseases".
Keywords: Stem Cell Transplantation; Animals; fúze buněk; Cell Lineage; Stem Cells; Germ Cells; Embryo, Mammalian; Pluripotent Stem Cells; buněčný rodokmen; Hematopoietic Stem Cells; buněčná diferenciace; lidé; Multipotent Stem Cells; transplantace kmenových buněk; kmenové buňky; zárodečné buňky; pluripotentní kmenové buňky; hematopoetické kmenové buňky; Cell Differentiation; zvířata; Cell Fusion; embryo savčí; multipotentní kmenové buňky; Humans